2022
DOI: 10.1002/smj.3435
|View full text |Cite
|
Sign up to set email alerts
|

Face‐to‐face interactions and the returns to acquisitions: Evidence from smartphone geolocational data

Abstract: Research Summary We examine the effect of face‐to‐face interactions between acquirers and targets before the acquisition announcements on acquisition returns. We argue that frequent interactions increase the target management's trust in the acquirer and benefit the acquirer by mitigating competition in the bidding process. For a sample of U.S. domestic acquisitions, we use smartphone geolocational data to measure the movement of people between merging companies in the months before the announcement. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…To capture some value, the focal acquirer needs to have an advantage over the latent acquirers of the target (Barney, 1986(Barney, , 1988. For instance, studies have shown that superior information about the target's value (Cai & Sevilir, 2012;Capron & Shen, 2007;Uysal et al, 2008), social relationships with the target's management (Testoni et al, 2022), uniquely valuable synergies with the target (Capron & Pistre, 2002), or vertical relationships with the target (Ahern, 2012) can provide an advantage in the bidding process, allowing the acquirer to leave less acquisition value to the target.…”
Section: Competition In the Market For Corporate Controlmentioning
confidence: 99%
“…To capture some value, the focal acquirer needs to have an advantage over the latent acquirers of the target (Barney, 1986(Barney, , 1988. For instance, studies have shown that superior information about the target's value (Cai & Sevilir, 2012;Capron & Shen, 2007;Uysal et al, 2008), social relationships with the target's management (Testoni et al, 2022), uniquely valuable synergies with the target (Capron & Pistre, 2002), or vertical relationships with the target (Ahern, 2012) can provide an advantage in the bidding process, allowing the acquirer to leave less acquisition value to the target.…”
Section: Competition In the Market For Corporate Controlmentioning
confidence: 99%
“…For instance, researchers with access to data on internal email traffic (Kleinbaum, 2012; Srivastava, Goldberg, Manian, & Potts, 2018) or, more recently, data on Zoom calls, could study intra‐firm networks of communication and coordination. Similarly, researchers could use data documenting movements of firms' executives to study interactions between firms, for instance, using cell phone data to examine face‐to‐face interactions between acquirers and targets (Testoni, Sakakibara, & Chen, 2022).…”
Section: Opportunities For Future Research On the Resource‐based Viewmentioning
confidence: 99%
“…Findings reported by Andrade, Mitchell and Stafford (2001) show that the percentage of hostile acquisitions fell from approximately 14% in the 1980s to only 4% a decade later. In a recent study, Testoni, Sakakibara and Chen (2022) assert that over the last three decades, most acquisitions have tended to be friendly transactions pursued by a single bidder. In an extensive meta-analysis, King et al (2021) discuss a relationship between continuous measures employed for target results and performance, without identifying any study that takes into account either the impact of distinct categories of target firms on post-deal results or the moderating influence of the target knowledge on this relationship in the context of the acquirer's full or partial strategy.…”
Section: Moving From Between To Within Heterogeneitiesmentioning
confidence: 99%
“…Findings reported by Andrade, Mitchell and Stafford (2001) show that the percentage of hostile acquisitions fell from approximately 14% in the 1980s to only 4% a decade later. In a recent study, Testoni, Sakakibara and Chen (2022) assert that over the last three decades, most acquisitions have tended to be friendly transactions pursued by a single bidder. In an extensive meta‐analysis, King et al.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%